ALMA-IMF. IX. Catalog and Physical Properties of 315 SiO Outflow Candidates in 15 Massive Protoclusters - Towner, A. P. M. (2023)
We present a catalog of 315 protostellar outflow candidates detected in SiO J = 5 - 4 in the ALMA-IMF Large Program, observed with ~2000 au spatial resolution, 0.339 km s-1 velocity resolution, and 2-12 mJy beam-1 (0.18-0.8 K) sensitivity. We find median outflow masses, momenta, and kinetic energies of ~0.3 M ⊙, 4 M ⊙ km s-1, and 1045 erg, respectively. Median outflow lifetimes are 6000 yr, yielding median mass, momentum, and energy rates of M˙ = 10-4.4 M ⊙ yr-1, P˙ = 10-3.2 M ⊙ km s-1 yr-1, and E˙ = 1 L ⊙. We analyze these outflow properties in the aggregate in each field. We find correlations between field-aggregated SiO outflow properties and total mass in cores (~3σ-5σ), and no correlations above 3σ with clump mass, clump luminosity, or clump luminosity-to-mass ratio. We perform a linear regression analysis and find that the correlation between field-aggregated outflow mass and total clump mass-which has been previously described in the literature-may actually be mediated by the relationship between outflow mass and total mass in cores. We also find that the most massive SiO outflow in each field is typically responsible for only 15%-30% of the total outflow mass (60% upper limit). Our data agree well with the established mechanical force-bolometric luminosity relationship in the literature, and our data extend this relationship up to L ≥ 106 L ⊙ and P˙ ≥ 1 M ⊙ km s-1 yr-1. Our lack of correlation with clump L/M is inconsistent with models of protocluster formation in which all protostars start forming at the same time.